2013
DOI: 10.1016/j.ecolind.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR derived ecological integrity indicators for riparian zones: Application to the Houille river in Southern Belgium/Northern France

Abstract: a b s t r a c tRiparian zones are central landscape features providing several ecosystem services and are exceptionally rich in biodiversity. Despite their relatively low area coverage, riparian zones consequently represent a major concern for land and water resource managers confirmed within several European directives. These directives involve effective multi-scale monitoring to assess their conditions and their ability to carry out their functions. The objective of this research was to develop automated too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…Because of the typical linear and narrow shape of the riparian zones, fieldbased monitoring involves sampling, high labor costs, and time-consuming travels (Debruxelles et al 2009;Myers 1989). The continuous improvement of the spatial resolution of remote sensing data combined with more powerful computer capacity and new geomatic procedures to extract information make the remote sensing approach more competitive (Alber and Piégay 2011;Carbonneau and Piégay 2012;Johansen et al 2010;Michez et al 2013;Roux et al 2014). The use of this very-high-resolution (VHR) imagery in a multitemporal approach is an emerging topic (Ardila et al 2012;Champion 2012;Lasaponara et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the typical linear and narrow shape of the riparian zones, fieldbased monitoring involves sampling, high labor costs, and time-consuming travels (Debruxelles et al 2009;Myers 1989). The continuous improvement of the spatial resolution of remote sensing data combined with more powerful computer capacity and new geomatic procedures to extract information make the remote sensing approach more competitive (Alber and Piégay 2011;Carbonneau and Piégay 2012;Johansen et al 2010;Michez et al 2013;Roux et al 2014). The use of this very-high-resolution (VHR) imagery in a multitemporal approach is an emerging topic (Ardila et al 2012;Champion 2012;Lasaponara et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Stout and Belmont () and Michez et al . (, 2014) focused primarily on floodplain features and did not fully characterize in‐channel riverscape units, while neither Piégay et al . (), Bertrand et al .…”
Section: Introductionmentioning
confidence: 95%
“…Michez et al . (, ) used LiDAR and photogrammetric digital surface models for the characterization of the riparian zones from local to regional scales in Wallonia (Belgium). Stout and Belmont () developed a semi‐automated selection of fluvial terraces and floodplain features from LiDAR data.…”
Section: Introductionmentioning
confidence: 99%
“…Riparian corridor features (Johansen et al 2010a, b;Michez et al 2013) LiDAR and High resolution multi-spectral Large wood and organic debris…”
Section: Riparian Vegetationmentioning
confidence: 99%
“…Moreover they found that SPOT-5 data were not useful for mapping most of the riparian attributes because of its coarse spatial resolution (pixel size = 10 m). More recently, Michez et al (2013) developed automated tools to quantify key riparian zone attributes for the assessment of the ecological integrity of the riparian zone at a network scale from a single aerial LiDAR dataset (Houille River, Belgium). This type of analysis offers the possibility of expanding the assessment of riparian zone vegetation to the entire Flanders region, which was completely mapped in 2014 with aerial LIDAR (13.000 km).…”
Section: Woody Debris (Smikrud and Prakash 2006)mentioning
confidence: 99%